Preparation of TiNi films by diffusion technology and the study of the formation sequence of the intermetallics in Ti–Ni systems. Issue 22 (24th September 2014) - Shao, Xi; Guo, Xianglong; Han, Yuanfei; Lin, Zhengjie; Qin, Jining; Lu, Weijie; Zhang, Di
Abstract: Abstract : This study presented a novel fabrication process for TiNi thin films by vacuum diffusion technology using reactive Ni/Ti/Ni multilayer thin films. The sandwiched thin films were prepared by chemical nickel plating. Ni/Ti/Ni multilayer films were heat treated for various diffusion times and temperatures and the influences of the temperature and diffusion time on the interdiffusion behavior of the Ti–Ni system were researched in detail. The results showed that a homogeneous TiNi thin film was obtained at 1173 K with a diffusion time of 4 h. Moreover, the formation sequence of the intermetallics in the Ti–Ni diffusion system was investigated by thermodynamic analysis and experiment. It was found that three compounds – TiNi3, Ti2 Ni, and TiNi – formed in the diffusion process at the Ti/Ni interfaces. More importantly, the nucleation of TiNi3 and Ti2 Ni was prior to that of TiNi because of the lower reaction Gibbs free energy and increasing interface energy of TiNi3 and Ti2 Ni.